2019
DOI: 10.1039/c9an00163h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the colorimetric detection of H2O2and ascorbic acid on polypyrrole coated fluconazole-functionalized POMOFs

Abstract: For the first time, a bifunctional colorimetric biosensing platform has been developed, based on a polypyrrole coated fluconazole-functionalized polyoxometalate-based metal–organic framework with ultrahigh stability for the enhanced detection of H2O2 and ascorbic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Therefore, the concentration of ascorbic acid was positively correlated with the change of absorbance of oxTMB. Figure 7 a showed that the relationship between the absorbance of mixed solution at 652 nm and the concentration of ascorbic acid (2–100 μM) was linear, and this upper limit was a relatively high concentration in the existing literature [ 24 ]. The linear regression equation was ΔA = 1.823C AA + 0.0906 (R 2 = 0.993), and the detection limit was 0.191 μM.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, the concentration of ascorbic acid was positively correlated with the change of absorbance of oxTMB. Figure 7 a showed that the relationship between the absorbance of mixed solution at 652 nm and the concentration of ascorbic acid (2–100 μM) was linear, and this upper limit was a relatively high concentration in the existing literature [ 24 ]. The linear regression equation was ΔA = 1.823C AA + 0.0906 (R 2 = 0.993), and the detection limit was 0.191 μM.…”
Section: Resultsmentioning
confidence: 86%
“…Here, we also discussed the effects of H 2 O 2 under light irradiation on the generation of •OH in solution using 3,3ʹ,5,5ʹ-tetramethylbenzidine (TMB) as the indicator. TMB can be oxidized to a blue product with a characteristic absorption peak at 652 nm by •OH [38]. As shown in Fig.…”
Section: +mentioning
confidence: 99%
“…So researchers have managed to combine it with MOF which also exhibited peroxidase‐responsive activity to synthesize a novel colorimetric biosensor [51,52] . In early studies, a series of simple, low‐cost, and highly sensitive colorimetric assays were derived for the detection of H 2 O 2 [53,54] . In recent years, it has been tried to be combined with other materials, thus creating many POMOFs‐based platforms for the detection of different biological materials, [55,56] Li et al.…”
Section: Application Of Pomof In the Field Of Biosensorsmentioning
confidence: 99%
“…[51,52] In early studies, a series of simple, low-cost, and highly sensitive colorimetric assays were derived for the detection of H 2 O 2 . [53,54] In recent years, it has been tried to be combined with other materials, thus creating many POMOFs-based platforms for the detection of different biological materials, [55,56] Li et al synthesized a POMOF/SWNT composite to develop a simple, fast-response and highly feasible "switch" for the detection of L -Cys colorimetric platform, which has the lowest detection limit (0.103 μM) for Lcysteine ( L -Cys) among all types of sensors to date. (Figure 7) [57] They synthesized the POMOF/SWNT composite nanoplatform using a simple ultrasound-driven periodic functionalization strategy, and PXRD patterns and IR spectra showed that its peak did not change after simulated peroxidase activity, and it maintained high enzymatic activity after 5 cycles of experiments, reflecting its good stability.…”
Section: Application Of Pomof In the Field Of Biosensorsmentioning
confidence: 99%